2021
DOI: 10.3390/antiox10020271
|View full text |Cite
|
Sign up to set email alerts
|

FK866 Protects Human Dental Pulp Cells against Oxidative Stress-Induced Cellular Senescence

Abstract: FK866 possesses various functional properties, such as anti-angiogenic, anti-cancer, and anti-inflammatory activities. We previously demonstrated that premature senescence of human dental pulp cells (hDPCs) was induced by hydrogen peroxide (H2O2). The present study aimed to investigate whether H2O2-induced premature senescence of hDPCs is affected by treatment with FK866. We found that FK866 markedly inhibited the senescent characteristics of hDPCs after exposure to H2O2, as revealed by an increase in the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Premature senescence is an acute and irreversible phenomenon induced by various stressors [ 37 , 38 ]. Thus, we analyzed the SA-β-gal activity, which is a well-accepted biochemical marker of cell senescence, in untreated and treated HTMCs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Premature senescence is an acute and irreversible phenomenon induced by various stressors [ 37 , 38 ]. Thus, we analyzed the SA-β-gal activity, which is a well-accepted biochemical marker of cell senescence, in untreated and treated HTMCs.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, citicoline modulated also the release of senescence-related pro-inflammatory cytokines ( Figure 6 ) [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…These data indicate that NAMPT may positively accelerate the differentiation of MDPC-23 cells without inducing cell proliferation. FK866 is known to exert antioxidant effects on other oxidative stress-related human diseases, such as viral infections, cardiovascular diseases, and oral mucosal diseases [ 24 ]. In contrast, the present results showed that the NAMPT inhibitor FK866 [ 25 ] decreased odontoblast formation in MDPC-23 cells ( Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of SA β-Gal, the expression of p53, and nuclear γH2AX foci are increased in disc cells by hydrogen peroxide [ 76 ]. In human dental pulp cells, hydrogen peroxide activates SA β-Gal activity, the p53/p21 Cip1 pathway, and the secretion of several inflammatory cytokines; collectively, these responses are termed the senescence-associated secretory phenotype (SASP) [ 77 ].…”
Section: Molecular Biological Relationships Between Oxidative Stress ...mentioning
confidence: 99%